Resolution of tonsillar herniation and syringomyelia after resection of supratentorial large meningioma - Chengjian Lou; Linkai Wang; Xiaoli Pan; Dan Xu; Yili Chen (Brain and Spine)
Background: Chiari malformation type I (CM1) with syringomyelia caused by supratentorial lesions is extremely rare, and the mechanism has not been well explained. Methods: A 25-year-old female patient with no significant medical history who presented with progressive pain in the left neck for one month. MRI examination showed a giant meningioma in the trigone of the lateral ventricle accompanied with CM1 and syringomyelia. Results: The patient underwent left parietal-occipital cortical approach surgery to remove the giant tumor in the trigone of the left lateral ventricle. The neck pain and left upper limb numbness were relieved immediately. CM1 and syringomyelia disappeared without posterior fossa decompression after surgical resection of the supratentorial tumor. Conclusion: This case shows that supratentorial space-occupying lesions (SOLs) causing acquired Chiari malformation (ACM) and syringomyelia is closely related to the tumor oppresses and increases the pressure of the posterior cranial fossa. Posterior fossa decompression was not needed for ACM and syringomyelia.